Cataract surgery after previous femtosecond laser intrastromal presbyopia treatment - Fitting, Anna; Rabsilber, Tanja Marina; Auffarth, Gerd U.; Holzer, Mike P. (Journal of cataract and refractive surgery, 2012)
We present a 58-year-old man who had cataract surgery in his right eye 8 months after femtosecond laser intrastromal presbyopia treatment (Intracor). The intraocular lens (IOL) power was calculated using the standard optical biometry data and the Holladay I formula without adjusting factors. Routine cataract removal was performed without complications followed by implantation of a monofocal IOL. The achieved spherical equivalent postoperatively was +0.25 diopters (D), which was +0.26 D different than the target refraction of the Holladay 1 formula. In conclusion, the IOL power calculation was predictable and the effect of the femtosecond intrastromal presbyopia treatment remained stable and improved further after cataract surgery: The pre-treatment uncorrected near visual acuity of 20/125 improved to 20/40 after treatment and to 20/25 six months after cataract surgery. Financial Disclosure No author has a financial or proprietary interest in any material or method mentioned.